Penyuluhan Dan Pendampingan Pencegahan Pernikahan Usia Dini Dengan Model Deep Dialogue Problem Solving Di Madrasah Aliyah Walisongo Gending Probolinggo - Umi Salamah (JPM PAMBUDI, 2019)
The phenomenon of child marriage in Gending Probolinggo is similar to Madurese. The majority of population, is descendants of Madura, made the baligh as the determinant of marriage. This community service aims to prevent the occurrence of child marriage. The import-of-prevention of effort, because child is vulnerable to reproduction, mental stress, and barriers to social interaction. In connection with that, the partisans who were subjected to counseling were MA and MTs Walisongo students, teachers, religious eaders / Kyai, and parents of students. The approach used was social, communication and personal approach with deep dialogue problem solving models. Based on these targets and approaches, was concluded (1) the same way of prevention and child care between persons and participants, (2) forms of collaboration and prevention of child labor and resources communication between participants and (3) agreement to open communication between participants and resource persons.